PP.42.09: ASSOCIATION BETWEEN DNA METHYLATION MARKS IN THE FTO GENE AND HYPERTENSION IN A HIGH CARDIOVASCULAR RISK MEDITERRANEAN POPULATION. (June 2015) - Sorlí, J.V.; Godoy, D.; Ortega-Azorín, C.; Asensio, E.M.; Carrasco, P.; Osma-Santiago, R.; Sánchez-Navarro, S.; Riera, C.; Portolés, O.; Corella, D.
Abstract : Objective: Epigenetic studies of hypertension are emerging and hold great promise of providing novel insights into the mechanisms underlying hypertension. Among epigenetic marks, DNA methylation is one of the most important. Although several studies have identified differences in methylation in some genes associated with hypertension, the results are preliminary and much work is needed. We focused on the fat mass and obesity (FTO) gene. It has been associated with obesity, type 2 diabetes and hypertension. The most relevant genetic variant in this gene is the rs9939609 T>A polymorphism, located in intron 1. Our aim was to study the association between methylation levels of the FTO gene and hypertension in a Mediterranean population. Design and method: We carried out a cross-sectional study in a sub-sample (n = 195: 98 men and 97 women) of participants in the PREDIMED-Valencia study (mean age 67 ± 7 y). DNA was obtained from blood and quantitative DNA methylation analysis was undertaken by matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry. We evaluated methylation levels in 21 CpG sites (13 in amplicon A and 8 in amplicon B) surrounding the rs9939609 polymorphism in intron 1 FTO gene (Chr16:53817859–53822719). Samples were analyzed by duplicate. Square root transformations were applied. Hypertension was defined and baseline and blood pressure was measured by triplicate with standard methods. Other clinical and lifestyle factors were determined. Multivariable adjusted models were used. Results: We detected some statistically significant association in the univariate analysis between DNA-methylation and diastolic or diastolic blood pressure (SBP or DBP, respectively). However, some of these correlations were lost after multivariable adjustment for sex, age and body mass index (BMI). The only significant association that remained statistically significant was between methylation levels of the CpG site 3 and DBP (P = 0.043). Moreover, this association was also significant when hypertension was considered. Thus, hypertensive patients has higher methylation levels (expressed as % of methylated C) than non-hypertensive subjects: 93.9% ± 0.7% vs 90.7 ± 1.5%; P = 0.046 in the multivariable adjusted model. Conclusions: In conclusion, we observed significant but small associations between FTO methylation marks and hypertension.